2018
DOI: 10.1097/coc.0000000000000400
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine and Celecoxib as a Promising Therapy for Thymic Neoplasms

Abstract: This case series suggests that capecitabine plus celecoxib may be an effective and well-tolerated treatment option for patients with thymic carcinoma. Further studies should be carried out to establish the efficacy of capecitabine plus celecoxib in thymic carcinoma, and to determine whether monotherapy with capecitabine would be similarly effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Toxicities observed were as expected for capecitabine. We previously reported durable responses to the combination in the subgroup of patients with thymic malignancies …”
Section: Resultsmentioning
confidence: 99%
“…Toxicities observed were as expected for capecitabine. We previously reported durable responses to the combination in the subgroup of patients with thymic malignancies …”
Section: Resultsmentioning
confidence: 99%
“…A recent study, on which our treatment plan was based, demonstrated some success in treating metastatic thymic epithelial neoplasms with capecitabine 1000 mg/m 2 two times per day and celecoxib 200 mg two times per day for 14 days on a 21-day cycle. Three patients in that study had thymic carcinomas, of which two had a complete response to therapy and one had a partial response 7…”
Section: Discussionmentioning
confidence: 96%